The mediating roles of cost leadership and cost focus strategies on innovation capabilities and export performance. Results from an emerging country - Eurico Navaia; António Moreira; Cláudia Ribau (Cogent Business & Management, 2024)
Although there are several studies analyzing how cost leadership and cost focus competitive strategies influence export performance, this article examines the relationship between innovation capabilities (ICs) and export performance (ExPf), as well as the mediating effects of cost leadership and cost focus competitive strategies among small and medium enterprises (SMEs) in Mozambique. Based on empirical survey data collected from 250 SME managers in Mozambique, we utilized Partial Least Squares Structural Equation Modelling (PLS-SEM) for data analysis. Findings demonstrate that both cost leadership and cost focus competitive strategies partially mediate the ICs-ExPf relationship. Furthermore, these competitive strategies enhance the direct effect of ICs on export performance. These results suggest that SMEs from emerging countries, such as Mozambique, can effectively develop ICs and leverage cost leadership and cost focus advantages to successfully compete in international markets. The implications of this study are significant for owners and managers of SMEs from emerging countries, as it provides valuable insights into the impact of cost leadership and cost focus advantages of firms' innovation capabilities. By understanding these relationships, SMEs can make more informed decisions and adopt more effective management approaches when seeking to compete in internationally, particularly among SMEs in emerging countries.
Keywords: L22; M16; 650; Innovation capabilities; export performance; competitive strategy; cost leadership; cost focus; Mozambique; emerging markets